Подождите немного. Документ загружается.
(3 ÷ 5) T
n
A ·i = b ⇒
a
13
a
14
a
23
a
24
· i =
−a
11
z −a
12
U
−a
21
z −a
22
U
.
A b
T
1
= T
2
= T
n
η = η
n
a
11
= a
11n
a
12
= a
12n
δ
a
13
a
14
a
23
a
24
· i =
−a
11
z −a
12
U
0
a
13
a
14
a
23
a
24
· i =
−a
11
z −a
12
U
−a
22
U
a
13
a
14
a
23
a
24
a
12
a
22
a
22
a
22
i
1
= i
2
.
x
0
ψ
1
=0 ψ
2
=0
T
i
a
11
a
12
P
load
=0 a
15
= a
25
=0)
1,765 0,968
T
1
= T
2
= T
a
11
a
12
T a
11
a
12
T
T
a
11
a
12
a
11
a
12
k
11
14,012
k
12
0,21
k
13
4,4
k
14
4,0
k
21
14,012
k
22
0,21
k
23
4,0
k
24
4,4
T a
11
a
12
u
1
= k
11
· z + k
12
· U
+ k
13
· (i
1
− i
o1
)+k
14
· (i
2
− i
o2
);
u
1
= k
21
· z + k
22
· U
+ k
23
· (i
1
− i
o1
)+k
24
· (i
2
− i
o2
) ,
U, i
1
,i
2
,i
o1
i
o2
U
= U/E i
1
= i
1
/E i
2
= i
2
/E i
o1
= i
o1
/E
i
o2
= i
02
/E
U + U
c
R
ext
= i
o1
+ i
o2
.
i
o1
i
o2
T = T
1
= T
2
1,765 0,968
T
P
load
=0 a
15
= a
25
=0
i
o1
i
o2
P
load
=0)
U
c
= 750
T =0,015
T =0,015
L
1
1, 35
L
2
1,25
C
1
2600
C
2
2500
E 850
R
ext
2,81 50
C
ext
5110 10000
P
load
0 200
P
load
=0 a
in+1
=0 m =2
d
ci
= −A · (U
out
− U
c
) − B · (i
1
− i
2
) − D · i
dif
− E ·
i
dif
U
2
out
− F · z,
i
dif
=(i
1
+ i
2
) − (i
o1
+ i
o2
)
L
1
L
2
0,5
P
load
=0
t =0,09 P
load
= 150
t =0,12 P
load
= 200
t =0,15 P
load
=0
m =1 P
load
=0